statistical analysis of modeling the conditions causing the exploitation of juveniles and their relationship to their crimes in Baghdad (المجلة العراقية للعلوم الاقتصادية, 2024)
The study deals with the most important factors affecting juvenile employment and their relationship to the crimes by using statistical analysis within the statistical program (spss). The Data of this analysis was obtained by questionnaire forms that were distributed to a sample consisting of 550 juvenile,their ages rang from (9-18) years .530 forms were correctly filled out, the rest of the 20 questionnaires were neglected because the answers were not complete. The sample covered Karkh and Rusafa districts, urban and rural cities, sub districts, displaced persons, and homeless ones (who live in the street). The forms were distributed to juveniles working in the industrial, agricultural, service, and streets of Iraqi society in the governorate of Baghdad, as well as 30 questionnaires for juveniles were distributed in the juvenile prison / Karkh, The data was modeled using multiple linear regression to analyze the causative and most influential conditions for the operation and exploitation of juveniles and their relationship to their crimes.